2022
DOI: 10.1021/acsaem.2c02597
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Carrier Separation in WO3/BiVO4 Photoanodes Achieved via Light Absorption in the BiVO4 Layer

Abstract: Photoelectrochemical (PEC) water splitting converts solar light and water into oxygen and energy-rich hydrogen. WO 3 /BiVO 4 heterojunction photoanodes perform much better than the separate oxide components, though internal charge recombination undermines their PEC performance when both oxides absorb light. Here we exploit the BiVO 4 layer to sensitize WO 3 to visible light and shield it from direct photoexcitation to overcome this efficiency loss. PEC experiments and ultrafast transient absorption spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(79 reference statements)
1
8
0
Order By: Relevance
“…A similar effect was reported by us to account for the enhancement of photocatalytic activity in a rutile–anatase bilayer system . Interestingly, the average thickness determined for this layer by the statistical morphological analysis of NTs in sample NT_#2 is about 65–85 nm, within a similar range of values to that found by Selim et al or Grigioni et al as optimal thickness for a stable and efficient photoresponse in WO 3 /BiVO 4 flat layer photoelectrodes. According to the scheme in Figure b, the equivalent thickness of the BiVO 4 semiconductor layer/aggregates in sample NT_#1 (ca.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A similar effect was reported by us to account for the enhancement of photocatalytic activity in a rutile–anatase bilayer system . Interestingly, the average thickness determined for this layer by the statistical morphological analysis of NTs in sample NT_#2 is about 65–85 nm, within a similar range of values to that found by Selim et al or Grigioni et al as optimal thickness for a stable and efficient photoresponse in WO 3 /BiVO 4 flat layer photoelectrodes. According to the scheme in Figure b, the equivalent thickness of the BiVO 4 semiconductor layer/aggregates in sample NT_#1 (ca.…”
Section: Resultssupporting
confidence: 87%
“…In addition to the evaluation of the PEC activity of NT electrodes, a critical point for assessment in this work has been to determine the influence of the thickness and morphology of the outer BiVO 4 shell layer on the OER yield. Recently, Kafizas et al 24 and Grigioni et al, 25 using transient absorption spectroscopy and planar WO 3 /BiVO 4 thin film heterojunction electrodes, have shown that photocurrent depends on BiVO 4 thickness, reaching a maximum yield for a thickness of 75 nm. Herein, we have compared the performance of the NT electrodes for a constant thickness of ITO and WO 3 layers but variable BiVO 4 layer thickness.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This value is rather low compared to other semiconductor oxides, consistent with the indirect nature of the CuWO 4 band gap. For instance, it is 4-fold lower than the α 420 value of BiVO 4 (6.7 × 10 4 cm −1 ), 38 and this implies that to absorb the same amount of 420 nm photons, a CuWO 4 electrode needs to be 4 times thicker than a BiVO 4 electrode. Interestingly the absorption coefficient for CuWO 4 at 420 nm is also ca.…”
Section: Photoelectrodes Preparationmentioning
confidence: 99%
“…200 nm. 20,30,31 This recombination path is indicated with red arrows in Scheme 2, which illustrates the prevailing charge transfer paths occurring in the WO 3 /BiVO 4 heterojunction under front-and back-side irradiation.…”
Section: Pec Characterization�linear Sweep Voltammetry (Lsv) Testsmentioning
confidence: 99%
“…Aiming at filling this gap, in this study we compare the water oxidation efficiency of WO 3 /BiVO 4 heterojunction photoanodes displaying either a nanoflake-like or a planar morphology but similar film thickness and optical properties. Through a systematic investigation based on the use of several physicochemical and PEC characterization techniques, we demonstrate that the wavelength-dependent performance limitations of planar electrodes, observed with increasing thickness of the WO 3 electron-carrier layer and leading to undesired photogenerated charge recombination, ,, can be successfully overcome by structure control of the WO 3 underlayer. Moreover, besides enhancing charge carriers separation on the 350–550 nm wavelength range, the here reported nanoflake-like heterojunction morphology allows preservation of the highly oxidizing valence band holes photoproduced in WO 3 by ultraviolet (UV) light, with an overall 6-fold larger photogenerated current and charge separation efficiency.…”
Section: Introductionmentioning
confidence: 99%